PROFESSOR WORK AT UNIVERSITY: DAILY PROBLEMS AND SOLUTIONS - Sergey A. Molodyakov (Высшее образование в России)
This article discusses issues related to daily work activities of a professor of engineering and particularly dwells on the problems of methodology and teaching methods. The author expresses his own position on some issues concerning distant e-education. It is treated as an important addition to traditional education. Distance courses have additional options for teaching students, and possess a shared location for all necessary learning materials in every discipline. The paper substantiates a need to apply international CDIO standards. There is also discussed a relation between education standard and professional standard. The educational programs should be designed according to the employers' requirements, particularly in such areas as computer engineering and programming. An example of an application of new methods in teaching the discipline «Computer and peripherals» is presented.